Synthetic Personas and Consumer Perception : The Impact of Virtual Influencers and Deepfake Ads in Next-Gen Brand Marketing - Khairnar, Apurva; Machek, Martin; Stříteský, Václav; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This research explores the impact of synthetic content, specifically virtual influencers and deepfakes, on brand marketing from both professional and consumer perspectives. Based on qualitative insights from five marketing professionals and quantitative data from 132 consumer respondents, this study investigates how synthetic content influences brand perception, consumer engagement, and trust. It also examines the challenges and ethical concerns associated with integrating virtual influencers and deepfake advertising into brand strategies. The findings indicate that while synthetic content can enhance brand visibility and control, its perceived authenticity significantly affects consumer trust and engagement. Virtual influencers are seen as innovative yet often lacking human relatability, while deepfakes offer efficiency but pose legal and ethical risks. The study highlights the importance of balancing technological innovation with human insights and transparency to maintain brand integrity and consumer loyalty.
Vedoucí práce: Martin Machek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses